Postcolonial Play in the Orient's Sandbox - Mukherjee, Souvik; Rizvi, Zahra (CyberOrient, 2023)
In this introduction to the special double issue, the guest editors outline their vision behind the work by giving a short overview of the orientalist bias in game studies, the postcolonialist turn in the field, and the need for South Asia‐centric scholarship to contribute to and invite South‐South discourse in games scholarship. This short introduction also introduces the various contributions to this double issue which range from academic articles to book reviews to comments.